The Future of Satellite Audio Drama - McMurtry, Leslie (Peripeti, 2015)
Technological advances, such as the podcast, have made the creation of audio drama easier, less expensive, and potentially more accessible and democratic in English-speaking countries such as the US, the UK, and New Zealand in the second decade of the twenty-first century. Using the case studies of Snape’s Diaries, Der Tickentocker, and Maudelayne, the article examines whether satellite audio drama will remain free to download and if so, how it will sustain momentum in an increasingly commercialized online world.